Comparison of push-out bond strength of mineral trioxide aggregate and calcium enriched mixture cement as root end filling materials - Alireza Adl; Fereshte Sobhnamayan; Omid Kazemi (Dental Research Journal, 2014)
Background: The purpose of this study was to compare the push-out bond strength of mineral trioxide aggregate (MTA) and calcium enriched mixture (CEM) as root end filling materials. Materials and Methods: A total of 40 root dentin slices (1 ± 0.2 mm) were prepared from freshly extracted human maxillary central teeth and their lumens were enlarged to 1.3 mm. The slices were randomly divided into two groups (n = 20). MTA and CEM cement were mixed according to manufacturer′s instruction and introduced into the lumens. The specimens were wrapped in pieces of wet gauze soaked in distilled water and incubated at 37°C for 3 days. The push-out bond strength was measured using a universal testing machine. The slices were then examined under a light microscope at ×10 magnification to determine the nature of bond failure. The data were analyzed using Mann-Whitney test (P < 0.001). Results: The mean push-out bond strength for CEM cement and MTA were 1.68 ± 0.9 and 5.94 ± 3.99 respectively. The difference was statistically significant (P < 0.001). The bond failure was predominantly of adhesive type in MTA group and cohesive type in CEM group. Conclusion: CEM cement showed significantly lower bond strength to the dentinal wall compared to MTA.